Cognitive profiles of adults with high-functioning autism spectrum disorder and those with attention-deficit/hyperactivity disorder based on the WAIS-III. (February 2017) - Kanai, Chieko; Hashimoto, Ryuichiro; Itahashi, Takashi; Tani, Masayuki; Yamada, Takashi; Ota, Haruhisa; Iwanami, Akira; Kato, Nobumasa
Highlights: The cognitive profiles of adults with high-functioning ASD and those with ADHD are described. Differences in VIQ–PIQ discrepancy were found between the two groups. The subtest of 'Verbal Comprehension' and two subtests of 'Freedom from Distractibility' were significantly higher in the ASD. The Picture Completion subtest was lower in the ASD. Abstract: The cognitive profile differences between adult patients with autism spectrum disorder (ASD) and those with attention-deficit/hyperactivity disorder (ADHD) are not well characterized. We examined the cognitive profiles of adults having either ASD (n = 120) or ADHD (n = 76) with no intellectual disabilities (IQ ≥ 70) using the Wechsler Intelligence Scale III (WAIS-III). Verbal Intelligence (VIQ) − Performance Intelligence (PIQ) difference discrepancies were detected between the two groups. Information subtest scores of the Verbal Comprehension index and Arithmetic and Digit Span subtests of the Freedom from Distractibility index were significantly higher in ASD than in ADHD, while the Picture Completion subtest was significantly lower in ASD. To our knowledge, this is the first study to evaluate the difference in the cognitive profiles of adults with ASD and those with ADHD based on the WAIS III with a large number of participants.